Invoking and supporting engineering student mathematical thinking in informal cooperative learning classroom - Baharun, Sabariah (Penerbit UTM Press, 2017)
Through our experience in teaching mathematics to engineering undergraduates, we found that students had numerous difficulties with the mathematics learned. Although our students have demonstrated the ability to answer standard or routine questions, there were still some inconsistencies between their ability to answer questions and their understanding of the concepts and the mathematical procedures they were using. In previous work, we had highlighted the importance of mathematical thinking and adopted suitable approaches in teaching and learning of engineering mathematics. However, innovative strategies were deemed necessary to assist students in their learning. In this paper, we will share how we transform our teaching practice to facilitate the development of students’ ability in understanding the various mathematical concepts, in reconstructing them as parts of a whole through cooperative learning. The approach allows them to develop efficient strategies in constructing new knowledge and be empowered with more successful ways of thinking about mathematics and solving problems. Here, we will share our experience in translating some of the theories into classroom practice through informal cooperative learning environment. Data were gathered through our own reflections, classroom observation, and interviews with the students. We will bring to light the findings on the students’ ability to solve problems related to the topics learned and discuss the implications for effective mathematics teaching and learning of prospective engineers.